2021
DOI: 10.1186/s12893-021-01154-x
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors and care measures of surgical site infection after cesarean section in China: a retrospective analysis

Abstract: Background Surgical site infections after cesarean section are very common clinically, it is necessary to evaluate the risk factors of surgical site infections after cesarean section, to provide evidences for the treatment and nursing care of cesarean section. Methods This study was a retrospective cohort study design. Patients undergone cesarean section in a tertiary hospital of China from May 2017 to May 2020 were identified, we collected the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
2
10
0
1
Order By: Relevance
“…Several studies have shown China’s cesarean section rate has been high in recent years [ 1 ]. Spinal anesthesia is still the preferred anesthesia method for cesarean section, with perfect analgesia, good muscle relaxation, and no adverse effects on the mother or fetus [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown China’s cesarean section rate has been high in recent years [ 1 ]. Spinal anesthesia is still the preferred anesthesia method for cesarean section, with perfect analgesia, good muscle relaxation, and no adverse effects on the mother or fetus [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical Site Infection (SSI) is a serious complication that can occur after surgeries [1][2][3][4][5][6][7]. One potential risk factor for SSI is HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Cesarean section surgery is a double-edged sword with some risk of adverse outcomes, and postoperative infection is one of the most common complications after cesarean section surgery. Although antibiotics have been widely used to prevent postpartum infection of cesarean section, the risk of abdominal incision infection, uterine incision infection, endometritis and urinary tract infection after surgery is still increasing [4]. In severe cases, sepsis, postpartum hemorrhage, shock and even life-threatening of patients may occur [5].…”
Section: Introductionmentioning
confidence: 99%